2001
DOI: 10.1091/mbc.12.6.1835
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of the Nucleus: A Novel Hog1p-independent, Pkc1p-dependent Consequence of Hypertonic Shock in Yeast

Abstract: Hypertonic shock of Saccharomyces cerevisiae activates the Hog1p MAP kinase cascade. In contrast, protein kinase C (Pkc1p) and the "cell integrity" MAP kinase cascade are critical for the response to hypotonic shock. We observed that hypertonic shock transiently relocated many, but not all, nuclear and nucleolar proteins to the cytoplasm. We hypothesized that the relocation of nuclear proteins was due to activation of the Hog1p kinase cascade, yet, surprisingly, Hog1p was not required for these effects. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 52 publications
3
32
0
Order By: Relevance
“…Activation of Mpk1 upregulates transcription of a series of genes involved in cell cycle progression and cell wall synthesis (Gustin et al 1998). While transcription of a great number of genes is mediated by the MAP kinases cascade in response to different cell wall impairments, little is known about other Pkc1 downstream effectors (Ketela et al 1999;Andrews and Stark 2000;Li et al 2000;Nanduri and Tartakoff 2001;Chai et al 2002;Valdivia and Schekman 2003).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of Mpk1 upregulates transcription of a series of genes involved in cell cycle progression and cell wall synthesis (Gustin et al 1998). While transcription of a great number of genes is mediated by the MAP kinases cascade in response to different cell wall impairments, little is known about other Pkc1 downstream effectors (Ketela et al 1999;Andrews and Stark 2000;Li et al 2000;Nanduri and Tartakoff 2001;Chai et al 2002;Valdivia and Schekman 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The downstream PKC1-mitogen-activated protein kinase (MAPK) cascade, consisting of Bck1, Mkk1/Mkk2, and Mpk1 kinases, phosphorylates transcription factors that regulate cell wall remodeling and cytoskeleton organization in polarized cell growth (Heinisch et al 1999). Although less well defined, several studies report evidence for other biochemical pathways branching out from Pkc1 (Ketela et al 1999;Andrews and Stark 2000;Li et al 2000;Nanduri and Tartakoff 2001;Chai et al 2002;Valdivia and Schekman 2003;Vilella et al 2005).…”
mentioning
confidence: 99%
“…When yeast experience hyperosmotic stress, the nucleolar protein Fpr3p relocalizes to the cytoplasm; however, over expression of Hog1 in this setting has a protective effect on Fpr3p nuclear localization (Nanduri and Tartakoff, 2001b). We examined the role of p38 MAPK in the nuclear transport factor response to osmotic stress using the p38 MAPK inhibitor, SB203580.…”
Section: Nuclear Transport and The Stress Responsementioning
confidence: 99%
“…In addition, hyper-osmotic stress of yeast has been shown to cause delocalization of nuclear proteins. This occurs in a Pkc1-dependent manner and can be inhibited by overexpression of Hog1 (Nanduri and Tartakoff, 2001b).In the course of analyzing the effect of stress signaling on nuclear transport, we found that the Ran protein gradient was disrupted in response to osmotic stress. To characterize the mechanism responsible for disruption of the Ran gradient, a battery of assays were used to define how the localization and activity of the nuclear transport machinery is affected by sorbitol stress signaling.…”
mentioning
confidence: 95%
See 1 more Smart Citation